A study on the construction of a nurse refresher training system in traditional Chinese medicine hospitals using the Delphi method - An, Ying; Xu, Huirong; Ma, Qiuxiao; Wang, Xiujun; Ding, Ying; Yang, Ruxin; Yang, Songbai (Frontiers in Public Health, 2025)
BackgroundThis study aims to develop a standardized advanced training system for nursing staff in traditional Chinese medicine (TCM) hospitals and verify its effectiveness.MethodsBased on literature review, training demand research, and semi-structured interviews, this study established a draft training system for TCM nursing staff. 12 experts refined the system through two rounds of correspondence using the Delphi method. Forty-five teachers engaged in clinical teaching were invited to evaluate the course quality, course setting, training programs, training effectiveness, teacher teaching quality, and full-score evaluation rate before and after the application of the training system.ResultsThe recovery rates for the two rounds of questionnaires were 100 and 91.67%, respectively, with authority coefficients of 0.938 and 0.953, and coordination coefficients of 0.233 and 0.239. The final training system included 15 first-level, 49 s-level, and 85 third-level indexes. Scores in the training effect evaluation significantly improved after applying the training system (p < 0.001).ConclusionIt is concluded that the training system constructed in this study is scientific, reliable, and valid, and can provide guidance for the training of TCM nursing staff.